2019
DOI: 10.1021/acsabm.9b00310
|View full text |Cite
|
Sign up to set email alerts
|

DNA-Peptide Amphiphile Nanofibers Enhance Aptamer Function

Abstract: The single-stranded DNA oligonucleotides known as aptamers have the capacity to bind proteins and other molecules and offer great therapeutic potential. Further work is required to optimize their function and to diminish their susceptibility to nuclease degradation. We report here on the synthesis and supramolecular self-assembly of DNA-peptide amphiphiles that form high aspect ratio nanofibers and display aptamers for the platelet-derived growth factor. The nanofibers were found to bind the growth factor with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…The system was proven to remain stable over 4 h in biofluids and exhibit specific cell targeting ability, leading to enhanced uptake by human B-cell leukemia cells. In addition, an extended study was reported from Samuel I. Stupp’s group, in which they coupled PDGF-BB-specific DNA aptamers to peptide amphiphile nanofibers (PANs) [ 17 ]. PAN is a material constructed by similar components of PAM, but assembles into an elongated nanofiber-like structure, which allows it to display high density of biological moieties on the surface.…”
Section: Aptamer-functionalized Non-biological Materials For Therapeutic Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The system was proven to remain stable over 4 h in biofluids and exhibit specific cell targeting ability, leading to enhanced uptake by human B-cell leukemia cells. In addition, an extended study was reported from Samuel I. Stupp’s group, in which they coupled PDGF-BB-specific DNA aptamers to peptide amphiphile nanofibers (PANs) [ 17 ]. PAN is a material constructed by similar components of PAM, but assembles into an elongated nanofiber-like structure, which allows it to display high density of biological moieties on the surface.…”
Section: Aptamer-functionalized Non-biological Materials For Therapeutic Applicationsmentioning
confidence: 99%
“…Aptamers have remarkable targeting specificities, so can benefit traditional nanocarriers through targeted delivery, increased drug permeability, reduced untargeted cytotoxicity, improved drug efficacy, and controllable drug capture and release [ 15 , 16 ]. Due to the large surface area, or EPR effects, some delivery materials in turn are able to enhance the functions of aptamers and protect them from nuclease degradation and quick filtration [ 17 ]. Moreover, the ease of introducing modifications on aptamers or nanomaterials, has further allowed researchers to design versatile drug delivery systems.…”
Section: Introductionmentioning
confidence: 99%
“…Aptamers, ssDNA oligonucleotides that selectively fold and bind to specific targets, such as proteins, have also been displayed on assemblies of peptide amphiphiles such as palmitoyl‐V 3 A 3 E 3 . [ 190 ] A 41‐nucleotide aptamer that binds the B chain of platelet‐derived growth factor (PDGF‐BB) that was presented in a multivalent display on PA nanofibers had a significantly increased binding affinity for PDGF‐BB compared to the monomeric aptamer. Presentation on the PA nanofibers also stabilized the aptamer to degradation by nucleases.…”
Section: Applicationsmentioning
confidence: 99%
“…In addition, Stupp’s team developed a supramolecular self-assembly system based on peptide amphiphiles (PAs, Table 4 ), which consist of a short β-sheet forming peptide sequence linked to a hydrophobic tail [ 74 , 75 , 76 , 77 ]. DNA-PA nanofibers formed by DNA-PA conjugates self-assembly displayed improved binding affinity to the target protein, enhanced nuclease-resistance as well as improved capacity to block PDGF-BB activity as compared with free aptamer [ 86 ]. Hernandez-Garcia et al synthesized P4 peptide by fusing P2 peptide for specific siRNA binding [ 87 ] and P3 peptide for structural switching from α-helix to β-sheet [ 88 ] via a spacer of two glycines [ 89 ].…”
Section: Sequence-defined Macromolecular Carriersmentioning
confidence: 99%